(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
It has been proved that the people of every age are capable to learn specific communication skills, which improve the interpersonal relationships and increase the success in the vocation. The skills required for communication with other people represent a combination of good interpersonal skills (ability to cooperate with the others) and intrapersonal skills (ability to manage the personal attitudes and emotions). Use of effective interpersonal communication strategies by caregivers in both personal and professional settings, may reduce stress, promote wellness, and therefore, improve overall quality of life. The interpersonal communication is immediate, direct communication between two or more persons, face to face, or with the mediation of some impersonal medium. We can determine it as an interaction in which a person presents some contents (information, messages) to another person in order to influence his/her behaviour or to participate in the creation of situations that will contribute to the changing of the personal attitudes and beliefs, that is, to help the adoption of certain facts and generalizations.